The Penerapan Aplikasi Cerdas Pendeteksi Stunting Pada Balita Bagi Kader Posyandu - Sari, Devi Pramita; Widodo, Sri; Mustofa, Khoirul (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat 2025, 2025)
Posyandu cadres are health providers who are closest to the community. One of the tasks of posyandu cadres is to address stunting. The problem faced by posyandu cadres in addressing stunting is the difficulty in determining the nutritional status and stunting status of toddlers. This is because this work is usually carried out by midwives at the Community Health Centre (Puskesmas). The objective of this community service project is to implement a smart application for detecting stunting in toddlers for posyandu cadres. The smart application includes: recording toddler medical records, automatically detecting toddler nutritional status and stunting, and displaying graphs of weight, height, and head circumference development. This community service project covers two main points. First is the implementation of a smart application for detecting stunting in toddlers for posyandu cadres, and second is training in the operation of the programme for posyandu cadres. The accuracy of the smart application for detecting stunting in toddlers is 96%. Meanwhile, the results of the evaluation of the feasibility of implementing the software using the PIECES method obtained a result of 83.8%. The results of the community service conducted at the Arumdalu Posyandu, Sangrahan Village, Grogol, Sukoharjo, show that Posyandu cadres are greatly assisted by the stunting detection software for infants using an intelligent system.